As marcas de intertextualidade na linguagem dos panfletos de doação de sangue - Souza, Bárbara Serrat Fernandes de (2009)
In this study we sought to verify the marks of intertextuality in the language of leaflets of donating blood in this corpus. Talk based on theoretical postulates of some authors: the ideology in the discourse to Orlandi (2000), Speech in the vision of Bakhtin (2006) The three stages of analysis of French discourse (AD) of French Foucault and Bakhtin; Arguments as Citelli (2004) The contributions of Bakhtin the analysis of discourse and dialogue to Brait (org), (1997), Metaphor and conceptual Metomínia to Lakoff & Johnson (1980) Verbal Interaction seconds Bakhtin, 2006); Genres of discourse, as Maingueneau (2005). The hypothesis that guided our research was that the marks of intertextuality serve as a resource facilitator for understanding the sentence. The search result has to confirm the hypothesis: the marks of intertextuality worked as a resource for facilitating the understanding of the statements in the corpus.